Spatial Patterns of Urban Growth - Does Location Matter? a Case Study of Nepal - Boris A. Portnov; Madhav Adhikari (European Regional Science Association (ERSA), 2006)
Between 1952 and 2001, the number of urban settlements in Nepal grew from 10 to 58, while their share in the country's population increased from 2.6 to 14.4%. However, the spatial distribution of urban growth was uneven. The fastest growing urban localities are situated near major population centers, close to highways, and in the vicinity of the In-dian border. Urban localities elsewhere exhibited sluggish economic growth and poor socio-demographic performance. Data for this analysis were drawn from databases maintained by Nepal's Central Bureau of Statistics; the Municipalities' Association; the Ministry of Local Development and its Department of Topographical Survey. In the GIS-assisted analysis, spatial reference data (e.g., distances between individual municipalities and major rivers, roads, international borders and major population centers) were matched against five performance indexes, viz. annual population growth, per capita in-come and expenditures of local municipalities, telephone ownership, number of primary schools, and number of industries.
Keywords: 330